EXPLORING STUDENTS’ MATHEMATICAL PROBLEM-SOLVING ABILITY ON SET TOPICS BASED ON SELF CONFIDENCE - Ali Shodikin; Yurizka Melia Sari; Alvenna Nursyafira (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Students’ problem-solving abilities are influenced by their self-confidence in learning mathematics. This study intends to investigate junior high school students' mathematics problem-solving abilities in terms of their self-confidence in the set content. Descriptive qualitative research methodology is employed. This research involved 32 students in 7th grade at SMP Negeri 2 Sukodadi, Lamongan. To focus on data analysis, 3 students were selected representing different levels of self-confidence, namely high, medium and low. Subject taking is based on the results of the scores on the self-confidence questionnaire that has been given. Questionnaires on self-confidence, tests of mathematical problem-solving abilities, and interview guidelines were the instruments employed. Based on the data analysis, it was found that there is a close relationship between self-confidence and mathematical problem-solving ability, that is, the higher the level of student self-confidence, the better the ability to solve mathematical problems. Conversely, if students’ self-confidence is lower, their mathematical problem-solving abilities will also be lower. This study emphasizes the importance of students' self-confidence to be grown in learning to support their mathematical problem-solving abilities.